2006
DOI: 10.5194/angeo-24-3557-2006
|View full text |Cite
|
Sign up to set email alerts
|

From pre-storm activity to magnetic storms: a transition described in terms of fractal dynamics

Abstract: Abstract. We show that distinct changes in scaling parameters of the D st index time series occur as an intense magnetic storm approaches, revealing a gradual reduction in complexity. The remarkable acceleration of energy release -manifested in the increase in susceptibility -couples to the transition from anti-persistent (negative feedback) to persistent (positive feedback) behavior and indicates that the occurence of an intense magnetic storm is imminent. The main driver of the D st index, the V B South elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

23
126
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 106 publications
(154 citation statements)
references
References 63 publications
23
126
1
Order By: Relevance
“…It is known that the Earth's magnetospheric dynamics is characterized by persistent dynamic correlations (e.g., Dobias and Wanliss, 2009) and near-criticality dynamics (e.g., Consolini, 2002;Wanliss and Uritsky, 2010), which are correlated features in self-organized critical systems in stationary conditions also away from the critical point (Woodard et al, 2007). Furthermore, the persistent character of the magnetospheric dynamics has been shown to undergo dynamical changes during magnetic storms and substorms (e.g., Wanliss, 2005;Balasis et al, 2006;Wanliss and Dobias, 2007). These points suggest that the more complex observed relation between the multifractional nature and the intermittent character of the geomagnetic fluctuations (see, e.g., Figs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is known that the Earth's magnetospheric dynamics is characterized by persistent dynamic correlations (e.g., Dobias and Wanliss, 2009) and near-criticality dynamics (e.g., Consolini, 2002;Wanliss and Uritsky, 2010), which are correlated features in self-organized critical systems in stationary conditions also away from the critical point (Woodard et al, 2007). Furthermore, the persistent character of the magnetospheric dynamics has been shown to undergo dynamical changes during magnetic storms and substorms (e.g., Wanliss, 2005;Balasis et al, 2006;Wanliss and Dobias, 2007). These points suggest that the more complex observed relation between the multifractional nature and the intermittent character of the geomagnetic fluctuations (see, e.g., Figs.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, it has been noticed that the self-similarity properties of these time series change when an intense magnetospheric/geomagnetic activity event approaches. For instance, Balasis et al (2006) have shown the occurrence of an interesting transition from the anti-persistent to the persistent character in the fluctuations of Dst index, which closely corresponds to a transition from a regime of quiet to one of high magnetospheric activity, characterized by the occurrence of intense geomagnetic storms. A similar behavior has been also documented in the case of the auroral electrojet (AE) index (e.g., Uritsky and Pudovkin,and discussed in a more general scenario, involving a near forced and/or self-organized criticality (FSOC) dynamics (Consolini, 1997;Uritsky and Pudovkin, 1998;Chang, 1999;Chang et al, 2003;Consolini and Chang, 2001;Consolini and De Michelis, 2002;Wanliss and Weygand, 2007;Wanliss and Uritsky, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This behaviour indicates that the external geomagnetic field is a multiscale process (Uritsky et al, 2001;Balasis et al, 2006). Considering current efforts in understanding the magnetic geo-environment and improving space weather forecasting, it is evident that the use of classical methods, such as the Fourier Transform for analysing the magnetic signal, or the geomagnetic index Dst, cannot yield any information on the temporal evolution of geomagnetic storm activity .…”
Section: Introductionmentioning
confidence: 99%
“…Some previous works have demonstrated the statistical self-affinity properties observed in the geomagnetic times series (Chang, 1999;Sitnov et al, 2001;Uritsky et al, 2001Uritsky et al, , 2006Kovacs et al, 2001;Lui, 2002;Wanliss, 2005a;Balasis et al, 2006;Wanliss and Dobias, 2007).…”
Section: Introductionmentioning
confidence: 99%